2013
DOI: 10.1002/ptr.5061
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and EGCG Exhibit Chemopreventive Effects in Cholangiocarcinoma Cells via Suppression of JAK/STAT Signaling Pathway

Abstract: Quercetin and epigallocatechin-3-gallate (EGCG) are dietary phytochemicals with antiinflammatory and antitumor effects. In the present study, we examined the effects of these two compounds on Janus-like kinase (JAK)/signal transduction and transcription (STAT) pathway of cholangiocarcinoma (CCA) cells, because CCA is one of the aggressive cancers with very poor prognosis and JAK/STAT pathway is critically important in inflammation and carcinogenesis. The results showed that the JAK/STAT pathway activation by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 33 publications
4
76
0
Order By: Relevance
“…They mediate anticancer effects with selective toxicity towards cancer cells [16]. The antitumor effect of flavonoids including luteolin, quercetin, and EGCG in CCA are mediated through the suppression of JAK/STAT signaling [9,17] and induction of mitochondrial cell death pathway [18]. In the present study, candidone showed a cytotoxic effect against two CCA cells, KKU-M156 and KKU-M213, in the micromolar range.…”
Section: Discussionsupporting
confidence: 48%
“…They mediate anticancer effects with selective toxicity towards cancer cells [16]. The antitumor effect of flavonoids including luteolin, quercetin, and EGCG in CCA are mediated through the suppression of JAK/STAT signaling [9,17] and induction of mitochondrial cell death pathway [18]. In the present study, candidone showed a cytotoxic effect against two CCA cells, KKU-M156 and KKU-M213, in the micromolar range.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, a compound with the ability to block the metastasis-associated steps could be a potential candidate for cancer chemoprevention and chemotherapy. It has been reported that the activation of STAT3 modulates the transcription of a variety of genes involved in the regulation of metastasis process, including ICAM-1 (Senggunprai et al, 2013) and vascular endothelium growth factor (Zhao et al, 2012). In this study, it was found that IL-6 increased the motility of CCA cells, and the specific JAK inhibitor, AG490, significantly decreased IL-6-dependent cell migration.…”
Section: Discussionmentioning
confidence: 56%
“…Cell migration was assessed using a wound healing assay as a method described previously (Senggunprai et al, 2013). Briefly, KKU-M156 cells (1.5 x 10 5 ) were seeded into a 24-well plate and incubated overnight in Ham's F12 medium, supplemented with 10% fetal calf serum.…”
Section: Wound Healing Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetes-induced glomerular hypertrophy in mice, low-dose ursolic acid ameliorated deterioration via suppression of diabetes-induced activations of STAT3, MAPK3/1 and JNK pathways [85]. Activation of the JAK-STAT pathway by IL6 and IFNG, was suppressed by pretreatment with quercetin and the effects involved STAT1 and STAT3 [73].…”
Section: Proteins Involved In Inflammationmentioning
confidence: 99%